Utilization of Evidence-based Intervention Criteria in U.S. Federal Grant Funding Announcements for Behavioral Healthcare - Miranda J. Lee-Easton MA; Stephen Magura PhD; Michael J. Maranda PhD (SAGE Publishing, 2022)
Recent U.S. federal government policy has required or recommended the use of evidence-based interventions (EBIs), so that it is important to determine the extent to which this priority is reflected in actual federal solicitations for intervention funding, particularly for behavioral healthcare interventions. Understanding how well such policies are incorporated in federal opportunity announcements (FOAs) for grant funding could improve compliance with policy and increase the societal use of evidence-based interventions for behavioral healthcare. FOAs for discretionary grants (n = 243) in fiscal year 2021 were obtained from the Grants.gov website for 44 federal departments, agencies and sub-agencies that were likely to fund interventions in behavioral health-related areas. FOAs for block/formula grants to states that included behavioral healthcare (n = 17) were obtained from the SAM.gov website. Across both discretionary and block grants, EBIs were required in 60% and recommended in 21% of these FOAs for funding. Numerous different terms were used to signify EBIs by the FOAs, with the greatest variation occurring among the block grants. Lack of adequate elaboration or definition of alternative EBI terms prominently characterized FOAs issued by the Department of Health and Human Services, although less so for those issued by the Departments of Justice and Education. Overall, 43% of FOAs referenced evidence-based program registers on the web, which are scientifically credible sources of EBIs. Otherwise, most of the remaining elaborations of EBI terms in these FOAs were quite brief, often idiosyncratic, and not scientifically vetted. The FOAs generally adhered to federal policy requiring or encouraging the use of EBIs for funding requests. However, an overall pattern showing lack or inadequate elaboration of terms signifying EBIs makes it difficult for applicants to comply with federal policies regarding use of EBIs for behavioral healthcare.